POPULATION HEALTH AS ONE OF THE SOCIETY OF SOCIO-ECONOMIC OF STATE DEVELOPMENT: ANALYSIS OF THE SITUATION AND TRENDS OF FINANCING - HARBYZUK, VALERYI; RUDNICHENKO, MYKOLA; OLINKEVICH, S. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article examines the features of the functioning and financing of the health care system of Ukraine. An analysis of the dynamics of changes in the health care financing system in 2015-2020. The main priorities of consolidated state budget expenditures for 2018-2019 have been identified. It is determined that the global quarantine restrictions related to the fight against the spread of coronavirus infection COVID-19 have significantly changed the approaches to financing the health care system in most developed countries. At the same time, even extraordinary measures did not allow to effectively overcome the consequences of the pandemic and its negative impact on the socio-economic development of states. This situation has become a significant challenge not only for the national security system of each country, but also highlighted the significant problems of inefficient allocation of state budget resources. Transformations of the health care system of Ukraine and changes are needed, but we can state the fact that public spending on health care in 2018-2020 is much slower than the economy. This situation is threatening not only for the health care system of Ukraine, it is problematic for the country's economy and for every citizen. The pandemic has shown that the development of socio-economic processes depends significantly on the health of workers, as both production and consumption are suspended in the face of the global threat of a pandemic. It is almost impossible to calculate the losses of economic systems properly, but most experts agree with the catastrophic consequences for the economy as a whole. The attention of institutional structures to the health care system and its proper functioning is the key to the development of every modern country.
Keywords: strategic adaptation; management system; tourist enterprises; transformation processes; external environment